OVERVIEW OF THE LEVEL OF SATISFACTION OF THE PATIENT'S FAMILY AT THE CHILDREN'S POLY OF INDRAMAYU HOSPITAL - Ali Musthofa; Kamsari; Novianda Ghina Nur Azizah (Jurnal Abdisci, 2024)
Success in providing hospital services is measured by the level of patient satisfaction and patient family, satisfaction is a person's feeling of pleasure or disappointment with the impression obtained when or after receiving services. The purpose of the study was to determine the picture of the level of satisfaction of the patient's family at the children's poly of RSUD Indramayu. This research uses quantitative research methods with a descriptive approach. The population in this study was the families of patients in the children's poly, for the sampling technique using accidental sampling as many as 85 respondents. Research instruments using questionnaires and data analysis using univariate. The results of this study found that as many as 48 respondents (56.5%) of patients' families were satisfied and 37 respondents (43.5%) of patients' families were dissatisfied, with dimensions tangible 65 respondents (76.5%) patient families are satisfied, reliability dimensions 68 respondents (80%) patient families are satisfied, responsiveness dimensions 68 respondents (80%) patient families feel dissatisfied, assurance dimensions 53 respondents (62.4%) and empathy dimensions 85 respondents (100%) patient families feel satisfied. The conclusion of this study illustrates the level of satisfaction of the patient's family at the children's poly of Indramayu Hospital, the results were obtained in the satisfied category of as many as 48 respondents (56.5%) and did not meet the minimum hospital service standards determined by the Ministry of Health of the Republic of Indonesia, which is ≥90%. It is recommended that medical personnel be able to make efforts or efforts in improving the health services provided.